2016
DOI: 10.1590/0001-3765201620150236
|View full text |Cite
|
Sign up to set email alerts
|

Feeding preference of Plutella xylostella for leaves treated with plant extracts

Abstract: Plutella xylostella L. is one of the main agents to cause damages to plants of Brassica genus, provoking negative impacts in cultures. The use of botanical extracts in plants protection has been related in literature, however, their use in the species analyzed in this study is not yet reported. We assessed the effect of aqueous and methanolic extracts of the species: Schinus terebinthifolius Raddi ( -branco), occuring in the state of Mato Grosso do Sul and whose feeding preference of P. xylostella larvae of 3r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…Aqueous extracts of C. adamantium, C. guazumifolia and C. xanthocarpa were prepared by maceration from leaves that were collected, dried in a forced circulation oven for 3 days at a maximum temperature of 40 °C (±1 °C) and then ground in a mill to obtain fine powder. n the present st shows the effe nd mean numb on (Amoabeng ul, 2012), and insects from plants, such as feeding inhibitors (Couto et al, 2016;Koul, 2005Koul, , 2008. In this line of study the genus Campomanesia interfered in the biological characteristics of P. xylostella.…”
Section: Preparation Of Aqueous Extractsmentioning
confidence: 52%
See 1 more Smart Citation
“…Aqueous extracts of C. adamantium, C. guazumifolia and C. xanthocarpa were prepared by maceration from leaves that were collected, dried in a forced circulation oven for 3 days at a maximum temperature of 40 °C (±1 °C) and then ground in a mill to obtain fine powder. n the present st shows the effe nd mean numb on (Amoabeng ul, 2012), and insects from plants, such as feeding inhibitors (Couto et al, 2016;Koul, 2005Koul, , 2008. In this line of study the genus Campomanesia interfered in the biological characteristics of P. xylostella.…”
Section: Preparation Of Aqueous Extractsmentioning
confidence: 52%
“…Studies involving plant extracts with medicinal properties have reported insecticidal properties such as mortality (Bandeira et al, 2013;Mishra & Singh, 2014;Peres et al, 2017) and feeding deterrence (Chandrashekharaiah et al, 2015;Couto et al, 2016); Deformities in adults, pupae and larvae of Plutella xylostella (Peres et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In oxidative stress environments, GSH can conjugate proteins, causing the formation of glutathionylated proteins (PSSG). High PSSG accumulation is often indicative of a deviant redox state and can cause cell damage and death [95, 96]. Hence, chemicals and drugs capable of enhancing GSH levels and restoring redox balance are of key importance to preventing and reducing RPE oxidative injury.…”
Section: Oxidative Stress and Nrf2 In Ocular Diseasesmentioning
confidence: 99%
“…A study by Couto et al (2016) evaluating the aqueous and methanolic extracts of the leaves of Annona coriacea Mart. and Schinus terebinthifolius Raddi.showed that these plants negatively affected the feeding of P. xylostella, reducing the leaf consumption of third instar larvae (caterpillars).…”
Section: Introductionmentioning
confidence: 99%
“…There are several plant families with the potential to be used for insect control (Camaroti et al, 2018), such as, Annonaceae (Ribeiro et al, 2018), Sapindaceae (Castillo et al, 2009), Meliaceae (Sapindal et al, 2017) and Rubiaceae (Peres et al, 2017). Highlighted among the substances useful for insect control are those with insecticidal action (Amoabeng et al, 2014), oviposition inhibitors (Torres et al, 2006), growth regulators (Koul, 2012), repellents (Koul, 2008), or those that only distance insects from the plants such as feeding inhibitors (Couto et al, 2016;Koul, 2005Koul, , 2008.…”
Section: Introductionmentioning
confidence: 99%